Proton magnetic resonance spectroscopy findings of a sacrococcygeal schwannoma. (1st January 2006) - Hascalik, S.; Celik, O.; Erdem, G.; Ara, C.; Kirimlioglu, H.
Abstract : Schwannoma is tumor of peripheral nerves, originating from Schwann cells. It is a rare nerve sheath tumor, which frequently occurs in the intracranial acoustic nerve and spinal nerves. We report on a 28-year-old woman who suffered from a large pelvic mass that was diagnosed to be sacrococcygeal schwannoma. The features of proton magnetic resonance spectroscopy (MRS) study are discussed. The magnetic resonance imaging instrument was a 1.5T, Gyroscan Intera with a body coil as a radiofrequency transmitter and a signal receiver. T2-weighted images were obtained under the following conditions—turbo spin echo (TSE) T2: turbo spin echo repeat time (TR) = 4500 msec, echo time (TE) = 96 msec. Single voxel MRS was performed by the point-resolved spectroscopy technique with a long TE (136 msec). MRS measurement was performed on two different parts of the tumor. As well as strongly elevated choline and lipid signals, the tumor spectrum showed increased N -acetylaspartate resonances. MRS can be used effectively in the preoperative diagnosis of retroperitoneal and pelvic masses, which demonstrate unusual clinical features.